Response of various oil palm materials (Elaeis guineensis and Elaeis oleifera × Elaeis guineensis interspecific hybrids) to bud rot disease in the southwestern oil palm-growing area of Colombia (2016)
Palms planted in an area with a high bud rot disease (BR) inoculum pressure were evaluated monthly for a six-year period to determine their tolerance, resistance, or susceptibility to the disease. Dura-type E. guineensis and OxG (E. oleifera × E. guineensis) interspecific hybrids Coari × La Me were evaluated. Of the two types of genetic material evaluated, the progenies of the E. guineensis palms showed the highest levels of incidence, reaching 90% affected palms in less than two years of evaluation. Although the hybrids showed susceptibility, they had a lower degree of affectation than the dura-type palms. The severity assessment of both genetic materials showed that the dura-type palms had the highest degree of affectation, reaching the highest values after over two years of evaluation. However, the hybrids, which were not homogeneous in terms of the level of severity, did not exceed, on average, severity level 2. According to the scale, severity level 2 is indicative of tolerance to the disease.